Change of treatment modalities over the last 10 years in pediatric patients with inflammatory bowel disease in Switzerland. Issue 10 (October 2018) - Guilcher, Katharina; Fournier, Nicolas; Schoepfer, Alain; Schibli, Susanne; Spalinger, Johannes; Braegger, Christian; Nydegger, Andreas
Abstract : Background and aim: During the past decade, several new drugs were approved for the treatment of pediatric inflammatory bowel disease (IBD). We aimed to evaluate if and how pharmacologic treatment options for pediatric IBD in Switzerland have changed over time. Patients and methods: Data from the pediatric Swiss IBD Cohort Study, a national prospective cohort study initiated in 2006, were analyzed. Patients were divided into two groups: patients with IBD diagnosis until 2009 (168 patients) and patients with IBD diagnosis in 2010 and after (210 patients). Both groups were analyzed regarding the past and the current therapies as well as need for surgery. Results: Overall, 378 pediatric patients with IBD were analyzed, of which 51.9% had Crohn's disease (CD) and 48.1% had ulcerative colitis/indeterminate colitis. Median age at diagnosis was 12 years. The majority (65.4%) of the patients with ulcerative colitis experienced pancolitis, whereas 45.4% of patients with CD presented with ileocolonic disease at diagnosis. A decreased use of corticosteroids in pediatric patients with CD can be found after 2010 ( P =0.041). Use of 5-aminosalicylic acid for patients with CD was dramatically reduced after the year 2010 (33.5 vs. 67.7% after 6 years of disease). A significant shift toward earlier use of biologicals could be shown after 2010 ( P <0.001). However, there was no significant decrease of surgery rate after 5 years of disease. Conclusion: In the past decade, a significant earlier use of anti-tumor necrosis factor-α agents in pediatric patients with IBD was observed with steroid-sparing effect in patients with CD. However, this change was not associated with reduction of surgery. Abstract : Supplemental Digital Content is available in the text.